Differential susceptibility of Dectin‐1 isoforms to functional inactivation by neutrophil and fungal proteases. Issue 6 (22nd January 2018) - Griffiths, James S.; Thompson, Aiysha; Stott, Matthew; Benny, Ankita; Lewis, Natalie A.; Taylor, Philip R.; Forton, Julian; Herrick, Sarah; Orr, Selinda J.; McGreal, Eamon P.
ABSTRACT: Patients with cystic fibrosis (CF) experience chronic or recurrent bacterial and fungal lung infections. Many patients with CF cannot effectively clear Aspergillus from their lungs. This may result in IgE sensitization and the development of allergic bronchopulmonary aspergillosis, or invasive infections, such as Aspergillus bronchitis. Lung disease in patients with CF is associated with neutrophil‐dominated inflammation and elevated levels of the serine protease, neutrophil elastase (NE). Various C‐type lectin‐like receptors (CLRs), including Dectin‐1 and Dectin‐2, are involved in the immune response to Aspergillus. Here, we show that purified NE cleaves Dectin‐1 in an isoform‐specific manner. Bronchoalveolar lavage fluid from patients with CF, which contains high NE activity, induces Dectin‐1 cleavage. Similarly, filtrate from a protease‐producing strain of Aspergillus fumigatus induces isoform‐specific cleavage of Dectin‐1. Dectin‐1 knockout (KO) cells and NE‐treated cells demonstrated reduced phagocytosis of zymosan, a fungal cell wall preparation. In addition, NE cleaves 2 other CLRs, Dectin‐2 and Mincle, and fungal‐induced cytokine production was reduced in Dectin‐1 KO cells, Dectin‐2 KO cells, and NE‐treated cells. Thus, Dectin‐1 and Dectin‐2 cleavage by NE and/or A.fumigatus –derived proteases results in an aberrant antifungal immune response that likely contributes to disease pathology in patients with CF.—Griffiths J. S., Thompson, A., Stott, M., Benny, A., Lewis, N. A., Taylor, P. R., Forton, J., Herrick, S., Orr, S. J., McGreal E. P. Differential susceptibility of Dectin‐1 isoforms to functional inactivation by neutrophil and fungal proteases. FASEB J. 32, 3385–3397 (2018). www.fasebj.org